KURIKULUM DALAM BINGKAI DESENTRALISASI: KAJIAN KEBIJAKAN PENDIDIKAN INDONESIA MASA REFORMASI - Mahdiyah, Dwi; Ba’in, Ba’in; Soeharso, R. (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This article examines the transformation of curriculum policy in Indonesia in the context of educational decentralization during the reform era. The 1998 reformation was an important turning point that drove the shift in the education system from centralization to decentralization, through strengthening the role of local governments in managing education. The curriculum as the main instrument of education has undergone significant changes along with changes in policies and the direction of national development. This study uses historical research methods with heuristic stages, source criticism, interpretation and historiography. The results of the study show that the implementation of the decentralization policy provides space for the development of a curriculum that is contextual and relevant to regional needs. However, its implementation cannot be separated from challenges such as limited human resources, inequality in access to education between regions, and dependence on central funding and policies. Therefore, synergy between the central and regional governments, as well as active participation of the community and educators, are the keys to the success of educational decentralization. The curriculum in the framework of decentralization is not only a technical tool for teaching, but also a reflection of the democratization process and efforts to improve the quality of national education in a sustainable manner.